2010
DOI: 10.1111/j.1744-7410.2010.00194.x
|View full text |Cite
|
Sign up to set email alerts
|

Paralarvae of the jumbo squid, Dosidicus gigas

Abstract: Abstract. The rhynchoteuthion stage of the jumbo squid, Dosidicus gigas, has morphological characteristics similar to the paralarvae of the purpleback squid, Sthenoteuthis oualaniensis, making it difficult to determine the locations, seasons, and conditions where spawning of jumbo squid occurs. In this study, 180 paralarvae of D. gigas were collected off the west coast of the Baja California peninsula and identified by sequencing a 369‐bp fragment of the cytochrome oxidase I gene. Of these, 77 specimens, 0.8–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
22
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 12 publications
(29 reference statements)
1
22
0
Order By: Relevance
“…Distinguishing different ommastrephid paralarvae using morphology is extremely difficult and molecular identification is being used increasingly frequently (e.g. Gilly et al 2006;Ramos-Castillejos et al 2010;Staaf et al 2013 Apart from the work on Ommastrephes bartramii and Dosidicus gigas outlined above, population studies have targeted a number of other ommastrephid species including Illex argentinus (Adcock et al 1999a(Adcock et al , 1999b, Illex coindetii (Dillane et al 2000) and Todaropsis eblanae (Dillane et al 2000(Dillane et al , 2005. Studies have also been conducted on Thysanoteuthis rhombus (Kitaura et al 1998), the only species within the family Thysanoteuthidae, which is commercially exploited in Japanese waters.…”
Section: Downloaded By [North Dakota State University] At 16:39 19 Nomentioning
confidence: 97%
“…Distinguishing different ommastrephid paralarvae using morphology is extremely difficult and molecular identification is being used increasingly frequently (e.g. Gilly et al 2006;Ramos-Castillejos et al 2010;Staaf et al 2013 Apart from the work on Ommastrephes bartramii and Dosidicus gigas outlined above, population studies have targeted a number of other ommastrephid species including Illex argentinus (Adcock et al 1999a(Adcock et al , 1999b, Illex coindetii (Dillane et al 2000) and Todaropsis eblanae (Dillane et al 2000(Dillane et al , 2005. Studies have also been conducted on Thysanoteuthis rhombus (Kitaura et al 1998), the only species within the family Thysanoteuthidae, which is commercially exploited in Japanese waters.…”
Section: Downloaded By [North Dakota State University] At 16:39 19 Nomentioning
confidence: 97%
“…Both species, however, have been identified off the Pacific coast of the Baja California Peninsula (Hernández-Rivas et al';Ramos-Castillejos et al, 2010 in the Gulf of California only the jumbo squid has heen reported to spawn (Gilly et al, 2006;Staaf et al, 2008;Camarillo-Coop et al, 2011), and, to our knowledge, no other adult ommastrephid has been described from this region, although adults of purplehack squid have been reported from the area near the mouth of this gulf (Olson and Galván-Magaña, 2002). In the southern hemisphere, the Peru Current System has yielded only jumbo squid paralarvae .…”
mentioning
confidence: 92%
“…The adult ranges of these 2 species overlap in the eastern tropical and subtropical Pacific (Roper et al, 1984), but the location and extent of spawning grounds of either species over this large region are not well established. Paralarvae of these species cannot be reliably distinguished morphologically; molecular techniques must be used (Gilly et al, 2006;Ramos-Castillejos et al, 2010). When molecular identification is not possible because of formalin preservation or other limitations, paralarvae in this broad geographic region are generally assigned to the "SD complex" (S. oualaniensis and D. gigas [Vecchione, 1999]).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Horizontal distances involved during this proposed migration would be at least 2750 km each way, conservatively assuming that squid migrate from the Pacific coast off Baja California where spawning occurs (27°N; Camarillo-Coop et al 2007, Ramos-Castillejos et al 2010 to Vancouver Island in British Columbia where adults are frequently encountered (49°N; Holmes et al 2008, Braid et al 2012. However, it is unknown how quickly Humboldt squid can cover such distances.…”
Section: Introductionmentioning
confidence: 99%